2008
DOI: 10.1182/blood.v112.11.157.157
|View full text |Cite
|
Sign up to set email alerts
|

Final Analysis of HOVON-50 Randomized Phase III Study on the Effect of Thalidomide Combined with Adriamycine, Dexamethasone (AD) and High Dose Melphalan (HDM) in Patients with Multiple Myeloma (MM)

Abstract: The randomised, open-label, phase III trial HOVON-50 was designed to evaluate whether the addition of Thalidomide to AD and HDM would prolong event-free survival (EFS) in patients with newly diagnosed MM. Patients with Salmon & Durie stage II or III, age 18–65 years inclusive were randomly assigned to arm A: 3 cycles of VAD or to arm B, the same regimen but with Thalidomide 200 orally, days 1–28 instead of Vincristine (TAD). Thalidomide was started at day 1 of the first TAD cycle and was stopped 2 weeks be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…(37) demonstrated that thalidomide maintenance provided no advantage in this subgroup of patients. Subsequently, other authors (38, 39) have published similar results. However, recently, Spencer et al.…”
Section: Discussionsupporting
confidence: 52%
“…(37) demonstrated that thalidomide maintenance provided no advantage in this subgroup of patients. Subsequently, other authors (38, 39) have published similar results. However, recently, Spencer et al.…”
Section: Discussionsupporting
confidence: 52%
“…More profound CR states, such as molecular remission, may be necessary to further improve outcomes, as recently reported after consolidation therapy with bortezomib, thalidomide, and dexamethasone in patients undergoing ASCT [14]. Thalidomide was the first novel agent used alone or in combination with steroids as consolidation or maintenance therapy after single or tandem ASCT for multiple myeloma in an attempt to improve disease control and has been the subject of six randomized clinical trials [4][5][6][7]15,16]. Significant improvements in PFS from thalidomide maintenance were observed in all six of those studies, and significantly increased OS was also noted in three of them.…”
Section: Discussionmentioning
confidence: 99%
“…In a Phase III prospective study conducted by the Dutch Group (HOVON 50), thalidomide–doxorubicin–dexamethasone (TAD) was compared with VAD as induction therapy for transplant-eligible patients. 18 , 19 Between November 2001 and May 2005, 556 patients were enrolled in the study. The primary endpoint was event-free survival (EFS).…”
Section: Thalidomide–doxorubicin–dexamethasonementioning
confidence: 99%